2016
DOI: 10.1109/jstsp.2016.2600516
|View full text |Cite
|
Sign up to set email alerts
|

Improving Wireless Physical Layer Security via Exploiting Co-Channel Interference

Abstract: Abstract-This paper considers a scenario in which a sourcedestination pair needs to establish a confidential connection against an external eavesdropper, aided by the interference generated by another source-destination pair that exchanges public messages. The goal is to compute the maximum achievable secrecy degrees of freedom (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Concluding, a total of two precoding vector pairs can be picked from C2, and as such an S.D.o.F. of 2 can be achieved [30], [31]. Based on Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concluding, a total of two precoding vector pairs can be picked from C2, and as such an S.D.o.F. of 2 can be achieved [30], [31]. Based on Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Therefore, by applying the precoding matrix design of [30], [31] to this equivalent helperassisted wiretap channel, the maximum S.D.o.F. can be achieved.…”
Section: A the Proposed Transmission Scheme Which Achieves The Maximmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1978, Cheong et al studied the degraded Gaussian eavesdropping channel and demonstrated that the security capacity of the Gaussian eavesdropping channel is the difference between Alice-Bob channel capacity and Alice-Eve channel capacity. Then, Csizar et al considered a more general channel model, 12,13 the system also has broadcast information and secret information for transmission, and the channel is no longer limited to the degraded channel; this article gives the broadcast information and secret information transmission rate capacity. There is also a corresponding study of the scheme of adding artificial noise (AN) to the SISO, but the SISO channel has no extra freedom to provide.…”
Section: Related Workmentioning
confidence: 99%
“…In [24], we determined the maximum achievable S.D.o.F. region of a two-user wiretap channel with a source destination pair exchanging confidential messages, another pair exchanging public messages, and a passive eavesdropper who is interested in the communications of the former pair.…”
Section: Introductionmentioning
confidence: 99%